Respuesta :
Answer:y=4
Step-by-step explanation: Simplifying
1.5y + -6 = 0
Reorder the terms:
-6 + 1.5y = 0
Solving
-6 + 1.5y = 0
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '6' to each side of the equation.
-6 + 6 + 1.5y = 0 + 6
Combine like terms: -6 + 6 = 0
0 + 1.5y = 0 + 6
1.5y = 0 + 6
Combine like terms: 0 + 6 = 6
1.5y = 6
Divide each side by '1.5'.
y = 4
Simplifying
y = 4
The equivalent equation, if 6 is factored out from the expression is 6(0.25y - 1)
Given a linear equation y = mx + b where b is the constant.
Given the linear equation f(y) = 1.5y - 6, we can see that 6 is the constant in the expression.
Factoring out 6 from the expression
[tex]f(y) = 1.5y-1.6\\f(y)=6(\frac{1.5y}{6}-\frac{6}{6} )\\f(y)=6(\frac{0.25y}{1} -1)\\f(y) = 6(0.25y-1)[/tex]
Hence the equivalent equation, if 6 is factored out from the expression is 6(0.25y - 1)
Learn more here: https://brainly.com/question/20953433